Pemeliharaan Fisik Taman Nostalgia Kota Kupang Provinsi Nusa Tenggara Timur - RUBA, VENANSIUS CH. FIRST; UTAMI, NI WAYAN FEBRIANA; ADNYANA, GEDE MENAKA (Jurnal Arsitektur Lansekap, 2015)
ABSTRACT Physical Maintenance in Nostalgia Park, Kupang City, East Nusa Tenggara Province Nostalgia Park is located in Frans Seda Street, Kupang City.  It is a city park built by the local government as the place for the National Peace Monument in Kupang. This park is managed by the local government and it has been the city park in Kupang, Nusa Tenggara Timur Province. The purpose of this research are to know the physical maintenance system of soft materials and hard materials,  the users’ perspective of the physical maintenance system, and  the obstacles in doing the physic maintenance in Nostalgia Park. This methods of research are done by doing observation, using questionaire to determine the visitors’ perceptions, identifying the physical maintenance system with the local government, and getting some literatures to complete the data of this research. Results of research indicated that the local government has done a good physical maintenance for soft materials and hard materials in Nostalgia Park. This can be seen by the result of the visitors’ perceptions and interview with the local government.   Key words: East Nusa Tenggara, Kupang City, Nostalgia Park, physical maintenance system